2019
DOI: 10.1002/sej.1318
|View full text |Cite
|
Sign up to set email alerts
|

Does VC backing affect brand strategy in technology ventures?

Abstract: Research Summary: The resource-based view of the firm characterizes brands as important resources for firm growth and competitive advantage. Existing studies offer theory and evidence that venture capital (VC) backing enhances the growth of new technology ventures along different dimensions. It is not clear, however, whether and how VC backing affects the development of brand assets. In a study of VC-backed and non-VCbacked nanotechnology ventures in the United Kingdom, we find a positive association between V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 107 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…They may suffer from severe liabilities of newness (Gruber 2004) and hence may file a trademark as a way to signal their seriousness and professionalism towards external stakeholders (Block et al 2015a). When it comes to investors, De Vries et al (2017) found that VC involvement is an important driver of trademark filing and the building of brand assets (Forti, Munari, and Zhang 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They may suffer from severe liabilities of newness (Gruber 2004) and hence may file a trademark as a way to signal their seriousness and professionalism towards external stakeholders (Block et al 2015a). When it comes to investors, De Vries et al (2017) found that VC involvement is an important driver of trademark filing and the building of brand assets (Forti, Munari, and Zhang 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we considered the relationship between VC and product-level effectiveness and efficiency, paying little attention to the relationship between VC and brand-level effectiveness and efficiency. A recent study found a positive effect of VC (versus non-VC) on the scope of technology ventures' brand assets (Forti et al, 2020). This study and our study provide a research gap to explore the different effects of CVC and IVC on more brand factors, such as brand diversity and popularity, or to examine their interaction effects with these brand factors.…”
Section: Limitations and Future Researchmentioning
confidence: 69%
“…For example, we considered the relationship between VC and product-level effectiveness and efficiency, paying little attention to the relationship between VC and brand-level effectiveness and efficiency. A recent study found a positive effect of VC (versus non-VC) on the scope of technology ventures' brand assets (Forti et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a vast literature on VC that spans strategy, entrepreneurship, and finance. Scholars in these fields have explored how venture capitalists (VCs) select portfolio firms, how they structure their investments (Ewens et al, 2022; Gompers et al, 2020; Kaplan & Strömberg, 2003; Tian, 2011), and how they contribute to new ventures' strategies (Blevins & Ragozzino, 2018; Forti et al, 2020) and financial performance (Conti & Graham, 2020; Dutta & Folta, 2016; Fitza et al, 2009; Hellmann & Puri, 2002). In contrast, we still know little about the investment strategies adopted by emerging entities other than traditional VCs.…”
Section: Introductionmentioning
confidence: 99%